MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA KARTU KATA BERGAMBAR PADA ANAK USIA 5 – 6 TAHUN DI TK AL MULK RANAH SINGKUANG KECAMATAN KAMPAR KABUPATEN KAMPAR - Nurzami Mardi; Isjoni Isjoni; Yeni Solfia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the beginning of improved reading skills in children ages 5 -6 years through the medium of pictorial word card in kindergarten AL Mulk Ranah Singkuang District Kampar Regenvy of Kampar. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are 5-6 years old children who totaled 15 children in kindergarten Al Mulk Ranah Singkuang. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the media picture card can improve reading skills at the beginning of children aged 4-5 years. It can be seen from the increase in the average percentage of literacy beginning in the first cycle of 45.0% which is the criterion begins to develop (MB) and increased by 63.8% in the second cycle be 73.71% which is at developing criteria to expectations (BSH). So, the media picture word cards can improve reading skills beginning 5 -6 year olds in kindergarten Al Mulk Ranah Singkuang Kampar District Kampar regency.    Keywords : Literacy Starters, Media Card Picture Words